Pengaruh Parameter Pemotongan dan Variasi Susunan Serat Terhadap Terbentuknya Delaminasi pada Proses Menggurdi Material Komposit Serat Nanas - Bambang Dwi Haripriadi; Ismet Hari Mulyadi (METAL: Jurnal Sistem Mekanik dan Termal, 2018)
Delamination is a failure occured during hole-making processes in machining. This can affect to rejection of the product. This failure is commonly found when drilling low machinability of plastic-based materials such as thermoplastic composites. Therefore, to eliminate that phenomena, the materials are necessary to be reinforced. In this case, addition of the fiber can strengthen the composites. Besides, the way the fibers were arranged when composite manufacturing is also responsible to improve tensile strength of the composites. Improving tensile strength would also improve the shear strength of the material. Shear strength is normally adopted as indicator for machinability of materials. However, relation of shear strength improvement of composites due to fiber arrangement has been rarely discussed. Using orthogonal arrays L27 based on Taguchi, this study investigated the effect fiber arrangement on formation of delamination in drilling pine-apple leaves reinforced composites. The results highlighted that effect fiber arrangement was significant on formation of delamination at exit sides of drilled holes. Reduced rasio delamination had been identified at this side. This inferr that strengthening effect would be a good strategy in reducing delamination at the exit sides.